Thalamic Metabolism and Restless Legs Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Researchers at University of Bologna, Italy, evaluated medial thalamus metabolism and structural integrity in 23 patients with restless legs syndrome and 19 healthy controls.